Iminodibenzyl class antipsychotics for schizophrenia: a systematic review and meta-analysis of carpipramine, clocapramine, and mosapramine - Kishi T (Dove Medical Press, 2014)
Taro Kishi, Shinji Matsunaga, Yuki Matsuda, Nakao Iwata Department of Psychiatry, Fujita Health University School of Medicine, Toyoake, Japan Background: We conducted a meta-analysis of the iminodibenzyl antipsychotics carpipramine, clocapramine, and mosapramine, which are classified as second-generation antipsychotics (SGAs) for schizophrenia treatment.Methods: We searched data that had been published in PubMed, the Cochrane Library databases, PsycINFO, CiNii, and the Japan Medical Abstracts Society up to August 29, 2014. Randomized controlled trials that compared iminodibenzyl antipsychotics with other antipsychotics in patients with schizophrenia were included. Odds ratios and standardized mean differences were evaluated.Results: We included four randomized controlled trials on carpipramine (number of patients [n]=290), six on clocapramine (n=1,048), and five on mosapramine (n=986) in the meta-analysis. There were no significant differences in the response rates or in the discontinuation rates either between carpipramine and the other pooled antipsychotics or between clocapramine and the other pooled antipsychotics. On the Positive and Negative Syndrome Scale, mosapramine’s positive subscale scores were superior to those of the other pooled antipsychotics (standard mean of difference =−0.22); however, on that same scale, there were no significant differences in total scores, negative scores, general subscale scores, response rates, or the discontinuation rates between mosapramine and the other pooled antipsychotics. Furthermore, the incidences of extrapyramidal symptoms and of hyperprolactinemia were significantly greater with mosapramine than with the other pooled antipsychotics.Conclusion: The pharmacological profiles of carpipramine and clocapramine, which are classified as SGAs, were similar to those of first-generation antipsychotics because there were no significant differences in efficacy and safety outcomes. However, mosapramine was associated with a greater risk of extrapyramidal symptoms and hyperprolactinemia than the other SGAs were, although it may be beneficial for the improvement of positive symptoms. Keywords: carpipramine, clocapramine, mosapramine, schizophrenia, meta-analysis